2022
DOI: 10.1155/2022/8414047
|View full text |Cite
|
Sign up to set email alerts
|

Arsenic Induces Continuous Inflammation and Regulates Th1/Th2/Th17/Treg Balance in Liver and Kidney In Vivo

Abstract: Numerous studies on arsenic-induced hepatonephric toxicity including cancer have been reported. Given that chronic inflammatory response and immune imbalance are associated with oncogenesis, we investigated whether arsenic could influence the hepatic and nephritic expression of inflammatory factors and the differentiation of T cells. Mice were exposed to NaAsO2 (0, 25, and 50 mg/L) for 1 and 3 months. Our data showed the destruction of the structure and inflammatory infiltration in the liver. The arsenic marke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 50 publications
(54 reference statements)
3
8
0
Order By: Relevance
“…Our data was in keeping with other studies, for instance, it was reported that arsenic caused renal histopathological changes of inflammatory cell infiltration, renal TECs desquamated, oozing blood, and glomerular atrophy. 16,43 NaAsO 2 -induced fibrosis in the kidney was also supported by previous studies where similar findings had been reported. 44,45 The adverse outcome pathway that how NaAsO 2 triggered kidney damage remains to be determined.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Our data was in keeping with other studies, for instance, it was reported that arsenic caused renal histopathological changes of inflammatory cell infiltration, renal TECs desquamated, oozing blood, and glomerular atrophy. 16,43 NaAsO 2 -induced fibrosis in the kidney was also supported by previous studies where similar findings had been reported. 44,45 The adverse outcome pathway that how NaAsO 2 triggered kidney damage remains to be determined.…”
Section: Discussionsupporting
confidence: 88%
“…15 In experimental animals, arsenic exposure can cause renal injury and interstitial fibrosis, including the pathology of mitochondria. 3,16,17 And the nephrotoxicity of arsenic was also confirmed by in vitro experiments. 14,18 Understanding the mechanism of arsenic exposure-induced renal fibrosis can help to the prevention and control of arsenic poisoning.…”
mentioning
confidence: 68%
“…In the course of antiviral treatment, CD4+CD25+ Treg frequency was declining in peripheral blood of CHB, and the decreasing degree of Tregs was greater in the HBeAg SC compared with that in the non-SC group, and the Treg frequency was higher in CHB subjects with active HBV replication [ 2 , 34 ]. Furthermore, the Treg frequency is positively correlated with serum ALT level [ 30 , 35 ], which was reconfirmed in our current study. The ALT levels usually reflect self-renewal metabolism of hepatocyte, and elevated serum ALT levels suggest the presence of active inflammation and the degree of hepatocyte injury caused by immune response against HBV [ 36 , 37 ].…”
Section: Discussionsupporting
confidence: 86%
“…Recent studies in mice showed that exposure to As activates the MAPK/NF-κB and NRF2 pathways in kidney. While activation of these pathways may improve cell survival, exposure to As also led to increased activity of myeloperoxidase and increased expression of inflammatory cytokines, such as IL-1α, IL-6, IL-12, and TNF-α, which may lead to an inflammatory response [ 118 , 119 ]. Furthermore, elevated expression of inflammatory cytokines was shown to disrupt homeostasis of helper T cell populations (Th1/Th2/Th17/Treg).…”
Section: Molecular Effects Of Environmental Toxicants On Ckd Progressionmentioning
confidence: 99%
“…The balance among T cells populations is critical to maintain proper immune function. Exposure to As alters the balance and leads to inflammation and immunosuppression [ 118 , 120 ]. Use of newer immunotherapeutics and their impact on kidney function is a new and expanding area of research.…”
Section: Molecular Effects Of Environmental Toxicants On Ckd Progressionmentioning
confidence: 99%